The Maize NBS-LRR Gene ZmNBS25 Enhances Disease Resistance in Rice and Arabidopsis - Xu, Yunjian; Liu, Fang; Zhu, Suwen; Li, Xiaoyu (Frontiers in Plant Science, 2018)
Nucleotide-binding site-leucine-rich repeat (NBS-LRR) domain proteins are immune sensors and play critical roles in plant disease resistance. In this study, we cloned and characterized a novel NBS-LRR gene ZmNBS25 in maize. We found that ZmNBS25could response to pathogen inoculation and salicylic acid (SA) treatment in maize, and transient overexpression of ZmNBS25 induced a hypersensitive response in tobacco. High-performance liquid chromatography (HPLC) analysis showed that, compared to control plants, ZmNBS25 overexpression (ZmNBS25-OE) in Arabidopsis and rice resulted in higher SA levels. By triggering the expression of certain defense-responsive genes, ZmNBS25-OE enhanced the resistance of Arabidopsis and rice to Pseudomonas syringae pv. tomato DC3000 and sheath blight disease, respectively. Moreover, we found little change of grain size and 1000-grain weight between ZmNBS25-OE rice lines and controls. Together, our results suggest that ZmNBS25 can function as a disease resistance gene across different species, being a valuable candidate for engineering resistance in breeding programs.